2019
DOI: 10.1111/fare.12415
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Military Family Resilience at the Transition to Parenthood: A Randomized Pilot Trial of an Online Version of Family Foundations

Abstract: ObjectiveThis article examines whether family resilience can be enhanced among military families via an online prevention program for military couples at the transition to parenthood.BackgroundMilitary families experience normative stressors similar to those of civilian families, as well as military‐specific stressors, such as deployment, frequent moves, and uncertainty.MethodParticipants were 56 heterosexual couples who, at the time of recruitment, were expecting their first child and were living together (re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 68 publications
1
11
0
Order By: Relevance
“…Tests of FF program effectiveness and mediational pathways in earlier waves of this study and other FF trials (Feinberg et al, 2009, 2020; Jones et al, 2018; Solmeyer et al, 2014) support the potential benefits for parents and children of targeting the coparenting relationship in a preventive manner. Moreover, the benefits of enhanced coparenting quality at family formation appear durable; we have reported long‐term impacts of FF as far out as 7 years after birth on teacher's reports of children's internalizing, externalizing, and academic adjustment (Feinberg et al, 2014).…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Tests of FF program effectiveness and mediational pathways in earlier waves of this study and other FF trials (Feinberg et al, 2009, 2020; Jones et al, 2018; Solmeyer et al, 2014) support the potential benefits for parents and children of targeting the coparenting relationship in a preventive manner. Moreover, the benefits of enhanced coparenting quality at family formation appear durable; we have reported long‐term impacts of FF as far out as 7 years after birth on teacher's reports of children's internalizing, externalizing, and academic adjustment (Feinberg et al, 2014).…”
Section: Introductionsupporting
confidence: 53%
“…This study found evidence that effective, early preventive intervention for families may not only have long‐term effects for all family members, but may also serve a protective function during unforeseen periods of stress and anxiety such as the early phase of the COVID‐19 pandemic. These results add to a growing body of evidence for the efficacy of FF’s strategic focus on enhancing coparenting; this evidence now extends across multiple delivery modalities, including in‐person and videoconference classes, an online self‐study e‐version (Feinberg et al, 2020), home visiting with low‐income parents (Ammerman et al, 2021), and school‐based classes for adolescent parents. Evidence of program effects also comes from pre‐/post‐evaluations of the FF program adapted for parents who already have children; one study was conducted with a parent peer mentoring version of FF for parents of young children with autism spectrum disorder (Hock et al, under review), and another home visit version adapted for Australian parents at risk for family violence (Giallo et al, under review).…”
Section: Discussionmentioning
confidence: 64%
“…For this reason, we recommend that practitioners offer services using multiple methods, such as offering make‐up lessons or offering services in a hybrid model where students can attend in‐person or online simultaneously. The benefits of providing web‐based programs for healthy relationship programming or enhancing coparenting have been studied in adult couples (Doss et al., 2016 ; Feinberg et al., 2019 ), but are needed with Latinx adolescent parents. However, we believe this might be a promising practice in helping students remain involved in school‐based programs.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the current study were recruited primarily from central Pennsylvania, as well as Delaware and Texas, between 2008 and 2012 for a randomized trial of Family Foundations, a transition to parenthood prevention program (Feinberg et al, 2016(Feinberg et al, , 2019Feinberg, Roettger, Jones, Paul, & Kan, 2015;Jones et al, 2018). Parents were eligible for the trial if they were at least 18 years of age and resided together.…”
Section: Methodsmentioning
confidence: 99%